Ag-Fe2O3 nanohybrids for photocatalytic degradation and antibacterial activity - AlZubaidi, Asaad; Pandit, Vikram; Jawale, Vivekanand; Gupta, Madhu; Late, Dattatray (Frontiers in Catalysis, 2025)
This study presents the synthesis and characterization of AgxFe2-xO3 nanoparticles as highly efficient photocatalysts and excellent antimicrobial agents. AgxFe2-xO3 nanoparticle synthesis was carried out through the sol–gel auto-combustion method. It was extensively characterized using X-ray diffraction (XRD), which confirmed the formation of crystalline α-Fe2O3 nanoparticles with a crystallite size of 22.23 nm. Ag-doped Fe2O3 has an average crystallite size of 23.08 nm. Fourier transform infrared (FTIR) spectroscopy provided insights about metal oxide bond formation and constant force for octahedral and tetrahedral sites, which suggest the location of the cation and anion. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed rhombohedral Ag-doped Fe2O3 nanomaterials with a uniform particle size around 20–50 nm, which matches the XRD results. UV–vis spectroscopy shows absorption shifting toward visible light for the AgxFe2-xO3 compared to pristine Fe2O3, indicating the utilization of the maximum light spectrum for efficient light harvesting in the visible region. AgxFe2-xO3 exhibited excellent stability and reusability for visible-light-driven photocatalytic dye degradation with a rate constant of 1.27 × 10−2 min−1, which is two-fold more than that of the pristine Fe2O3 (0.51 × 10−2 min−1). AgxFe2-xO3 was also found to be more efficient in inhibiting the growth of Proteus mirabilis with a 16 mm zone of inhibition.